Dying neurons conduct repair processes in the injured brain through osteopontin expression in cooperation with infiltrated blood monocytes. Issue 4 (9th December 2020) - An, Jiawei; Yang, Haijie; Yang, Esther; Chung, Sooyoung; Kim, Dae‐Yong; Jou, Ilo; Park, Sang Myun; Kim, Byung Gon; Chwae, Yong‐Joon; Joe, Eun‐Hye
Abstract: The brain has an intrinsic capacity to repair injury, but the specific mechanisms are largely unknown. In this study, we found that, despite their incipient death, damaged neurons play a key repair role with the help of monocytes infiltrated from blood. Monocytes phagocytosed damaged and/or dying neurons that expressed osteopontin (OPN), with possible subsequent activation of their inflammasome pathway, resulting in pyroptosis. During this process, monocytes released CD63‐positive exosome‐like vesicles containing OPN. Importantly, following the exosome‐like vesicles, neuron and astrocyte processes elongated toward the injury core. In addition, exosomes prepared from the injured brain contained OPN, and enhanced neurite outgrowth of cultured neurons in an OPN‐dependent manner. Thus, our results introduce the concept that neurons in the injured brain that are destined to die perceive the stressful condition and begin the regeneration processes through induction of OPN, ultimately executing the repair process with the help of monocytes recruited from the circulation. Main Points: Dying neurons express osteopontin (OPN). Monocytes phagocytose dying neurons, undergo pyroptosis, and produce exosomes containing OPN(+) neuronal cells. Exosomes from the injured brain facilitate elongation of neurite and astrocyte processes.